Increasing Utilization of Government-Assisted Patchouli Distiller In West Pasaman Regency - Ahmad, Hafizh; Fitriana, Widya; Analia, Devi (JTI: Jurnal Teknik Industri, 2024)
The patchouli plant has great economic potential for society because it is one of the priority industries. The government continues to encourage the development of the patchouli oil agro-industry. One of the supports provided by the government to improve the quality of patchouli oil is the provision of stainless-steel distiller to several farmer groups in West Pasaman. Unfortunately, this distiller is no longer used even though it is still in good condition. This research proposes appropriate policy directions to increase government-assisted patchouli distillation equipment use in West Pasaman Regency. The policy direction was formulated based on the solution to the obstacles using the Fuzzy Delphi Method (FDM). From the research results, stainless steel distillers are generally better than conventional ones. Still, farmers in West Pasaman Regency do not use government-assisted distiller one hundred percent. Farmers have switched to using traditional distillation. The obstacles to the use of stainless-steel distiller in West Pasaman Regency are community habits, the large capacity of the distiller, the remote location of the distiller, ownership status, the permanent nature of the distiller, the design and mastery of the distiller, technology, and changes in economic sectors. The policy directions related to assistance with stainless steel distiller obtained from the results of this research are: a). The government involves experts in designing and procuring distiller. b). The government conducted a comparative study to determine the appropriate distillation tool specifications. c). Create a policy regarding the number of members of farmer groups. d). Provide technical guidance to farmers regarding the use of stainless-steel distillers. e) Formation of sales cooperatives.  Keywords: Patchouli Oil, Stainless Steel Distiller, Fuzzy Delphi Method, Policy